Propuesta de un módulo integrador STEM-EpC sobre el aprovechamiento de agua lluvia para una escuela rural multigrado unitaria (2017)
This work arose from the difficulties observed in the teaching-learning process in one-room rural schools and the need to train competent young people who may develop skills for the twenty-first century. Thus, an integrative proposal STEM-EpC is presented. In this, both the STEM areas, as well as the grades from first to fifth ones in elementary, even kindergarten, are integrated through a module of two units about the collection, exploitation, and maintenance of rainwater. For the design of this module was taken into account: the integrating principles of the STEM pedagogy (Science, Mathematics, Technology and Engineering), the parameters of the Teaching for Understanding, EpC, in relation to the use of conducting wires and phases in the planning, and national curriculum guidelines for elementary primary for the STEM areas. The research was performed using a qualitative approach, that is the phenomenography. The results were obtained through individual and group interviews, class observations and student performances. These results were analyzed in an inductive way and a outcome space was obtained, consisting of 24 descriptive codes corresponding to the different ways in which the knowledge was presented, these were reorganized into four main categories. To these categories we call them "Activators" since they were ways of knowledge that activated the understanding, these "Activators" are: application in context, basic concepts, description of processes and understanding of concepts, being the Application in context the one which generated the rest ones. Thus, through the STEM-EpC integrator module, an understanding of the cross-sectional concepts of the STEM areas was demonstrated in an applicable and innovative way, through a practical, striking theme and in the school context. In addition, important skills were developed for this century and the needs and technological advances of nowadays.